Evaluasi Kualitas Layanan Website PT. Kereta Api Indonesia (Persero) terhadap Kepuasan Pengguna Menggunakan Webqual 4.0 dan Importance-Performance Analysis (IPA) - Izzati Dalilah; Ari Kusyanti; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Online trading is growing rapidly especially in Indonesia. PT. Kereta Api Indonesia (Persero) is one of the companies that provide online ticketing service. This study aims to evaluate the quality of website services PT. Kereta Api Indonesia (Persero) to user satisfaction using Webqual 4.0 and Importance-Performance Analysis (IPA) methods. Data collection techniques used in this study is a questionnaire with a sample size of 109 respondents. Descriptive statistical results show that the value of Usability, Information Quality, and Service Interaction Quality fall into the high category. The result of hypothesis testing shows that Usability, Information Quality, and Service Interaction Quality have positive and significant influence to user satisfaction (User Satisfaction) website of PT. Kereta Api Indonesia (Persero). The IPA quadrant analysis result shows that the navigation indicator needs to be improved because it is considered very important for the user but the perceived performance is not satisfactory.